Islamic Legal Perspective on Data of Child Victims of Sexual Violence: A Case Study of the Indonesia’s Court - Gurusi, La; Mansyah, Muh Sutri; Lee, Kirsty; Purnamasari, Yety; Alfajar, Subhan (De Jure: Jurnal Hukum dan Syari'ah, 2024)
The Case Tracking Information System (SIPP), established by the Supreme Court, is designed to facilitate the tracking of legal cases. However, concerns have arisen regarding data leakage of victims of sexual violence. This study seeks to analyse and evaluate the protection of personal data of victims of sexual violence published in the SIPP Court, particularly from an Islamic law perspective. Employing a socio-legal research method, the study integrates case, statutory, and conceptual approaches. Primary legal materials include laws and regulations relevant to victim protection, while secondary legal materials are sourced from relevant journals, books, and literature. The analysis was performed using a descriptive technique with grammatical and systematic interpretations. The results of the study show that five laws (Witness and Victim Protection Law, Sexual Violence Crime Law, Personal Data Protection Law, Juvenile Criminal Justice System Law, and Child Protection Law) regulate victim confidentiality to prioritise the best interests of children as the next generation of the nation. Despite these legal provisions, practical discrepancies persist. For example, in the SIPP of the Baubau District Court, sensitive details such as victims’ names are accessible, whereas the Aceh District Court only displays anonymised data, using aliases like "child witness." From the Islamic perspective, as derived from the Quran and Hadith, Muslims are prohibited from approaching adultery, and people who commit adultery will be punished both in this world and in the hereafter. The implication of personal data protection for victims of sexual violence, associated with Maqashid Syariah, is that the protection of the soul (hifz al-nafs) and mind (hifz al-‘aql) of children is part of the collective responsibility borne together by the family, society, and government. Therefore, it is important to reevaluate and reconstruct the protection of child victim data in SIPP